INVESTIGATING THE ROLE OF CBCL LISTENING E-MODULE IN FOSTERING 21ST CENTURY SKILLS: AN EXPERIMENTAL STUDY - Imroatul Ma'fiyah; Riyani Riyani; Carrisa Rahma Yuliana (University of Kuningan, 2025)
This study examines the effectiveness of a Case-Based Collaborative Learning (CBCL) listening e-module in enhancing the 21st-century skills of English Language Teaching (ELT) students, specifically focusing on critical and creative thinking skills. Utilizing an experimental design, 38 students participated, with an experimental group using the e-module and a control group following traditional instruction. Results from pre- and post-tests demonstrated significant improvements in the experimental group. Additionally, students’ feedback revealed high satisfaction with the module’s content relevance, multimedia integration, and scaffolded activities. These findings suggest that CBCL-based e-module is an effective tool for fostering students’ creative and critical thinking, contributing to innovative teaching practices in ELT.